From Frozen Peas To Fashion Pieces - Hedlund,Clara; Jeanson,Elin (2025)
The purpose of this thesis is to explore how consumers perceive and interpret limited-edition clothing merchandise released by fast-moving consumer goods (FMCG) brands as a far brand extension strategy, and whether it influences the parent brand image. The study uses the Swedish FMCG brand Eldorado as a single case to examine how limited-edition clothing merchandise, incorporating recognizable brand elements, shape consumer perceptions and interpretations. The research problem is grounded in a growing trend where brands from traditionally low-involvement categories, particularly FMCG, extend into high-involvement, identity-driven domains such as fashion. While brand extension is a well-established strategy, there is an uncovered gap on how far brand extensions with low category fit are perceived and interpreted by consumers, especially when they are launched as limited-edition collections and incorporate recognizable brand elements. Moreover, little is known about whether and how these interpretations influence the image of the parent brand. With an ontological stance in relativism, this thesis adopts an epistemological perspective of social constructivism. In alignment with these foundations, a qualitative case study design was employed. Thirteen semi-structured interviews were conducted with young Swedish consumers to capture their subjective perceptions and interpretations. The research reveals that consumers interpret the extension through cultural references, perceiving the merchandise as, among others, “fun”, “ironic”, and “trendy”, in strong contradiction to the parent brand’s usual associations. The findings also reveal that the divergent perceptions and interpretations of the clothing merchandise, compared to how consumers typically describe Eldorado, appear to stem from three contrasts related to expectations and perceived outcomes. These are: (1) contrast in category and context, (2) contrast in perceived effort in visual presentation, and (3) contrast in social value. Despite generating positive associations with the extended merchandise, these perceptions do not appear to enhance the parent brand’s image in its original FMCG context. Furthermore, the study emphasizes the role of limited editions in mitigating the risks associated with low-fit extensions, and highlights the importance of visual presentation. As a result, this study contributes to the literature on limited edition far brand extensions and their influence on parent brand image. The study also offers managerial implications by outlining both the opportunities and risks of using clothing merchandise as a far brand extension. For managers considering this strategy, it is crucial to understand the target audience’s cultural references in order to effectively assess its strategic potential.
Keywords: Far Brand Extension; Fast-moving Consumer Goods (FMCG); Limited Edition; Clothing Merchandise; Feedback effect; Forward Effect; Ironic Consumption; Brand Image